AN AREA OF RIGHT TRIANGLE FOR TRIGONOMETRY - IDRIS, MOCHAMMAD; SHIDDIQ, MOHAMMAD MAHFUZH; ERIDANI, ERIDANI (Jurnal Matematika UNAND, 2023)
In this paper, we shall investigate formula of tangent function through determination of area of right triangle and rectangle. The consequence of this formula is used to obtain the other two trigonometric function, i.e. sine and cosine functions. Moreover, we also reprove Pythagorean theorem.